Cultivating STEM engagement among African American youth: an exploration of secondary students' voices - Roxanne Hughes; Adam Baptiste; Shannon Hall-Mills (Springer, 2024)
Abstract In the United States, individuals who identify as Black are severely underrepresented in science, technology, engineering and mathematics (STEM) disciplines. This underrepresentation begins as early as middle school due to the stereotype of successful STEM students being white and male thus affecting Black students sense of belonging in STEM. The goal for this exploratory qualitative study was to understand the experiences of Black students in their science classes. Our choice of focus groups empowered these students, who have historically been missing from educational policy decisions, by providing them an opportunity to be part of the change they want to see in their schools. The results indicate that participants could see potential relevance in science and math classes but the structure of their current science classes (e.g., neglect and lack of care from teachers) affects their ability to actually experience this relevance. Despite this, many of our participants understood their value and believed that they "deserve more," which shows that we can improve the experiences for Black students in STEM and increase their representation in these disciplines.